Blackberry-Like Doxorubicin Loaded Hyaluronic Acid/Zinc Phthalocyanine Loaded Mesoporous Silica Nanocomposites for Long-Term Tumor Photodynamic and Chemotherapy Synergistic Therapy - Du S; Li L; Kou J; Zhu T; Song Z; Zhan Y; Wu D; Zhan W (International Journal of Nanomedicine)
Shangting Du,1 Lingyu Li,1 Junhao Kou,2 Tianyi Zhu,1 Zhenyi Song,2 Yonghua Zhan,3 Daocheng Wu,4 Wenhua Zhan1,5 1Department of Radiation Oncology, General Hospital of Ningxia Medical University, Yinchuan, Ningxia Hui Autonomous Region, 750004, People’s Republic of China; 2School of Pharmacy, Xi’an Medical University, Xi’an, Shaanxi, 710021, People’s Republic of China; 3School of Life Science and Technology, Xidian University and Engineering Research Center of Molecular and Neuro Imaging, Ministry of Education, Xi’an, Shaanxi, 710071, People’s Republic of China; 4Key Laboratory of Biomedical Information Engineering of the Ministry of Education, School of Life Science and Technology, Xi’an Jiaotong University, Xi’an, Shaanxi, 710049, People’s Republic of China; 5State Key Laboratory of Pathogenesis, Prevention and Treatment of High Incidence Diseases in Central Asia, Xinjiang Medical University, Urumqi, Xinjiang Uygur Autonomous Region, 830054, People’s Republic of ChinaCorrespondence: Daocheng Wu, Key Laboratory of Biomedical Information Engineering of the Ministry of Education, School of Life Science and Technology, Xi’an Jiaotong University, Xi’an, Shaanxi, 710049, People’s Republic of China, Email wudaocheng@mail.xjtu.edu.cn Wenhua Zhan, Department of Radiation Oncology, General Hospital of Ningxia Medical University, Yinchuan, Ningxia Hui Autonomous Region, 750004, People’s Republic of China, Email zhanwhgood@163.comBackground: The co-loading of zinc phthalocyanine (ZnPc) and doxorubicin (DOX) on a nanocarrier for tumor photodynamic therapy (PDT)-chemotherapy (CT) synergistic therapy is an effective approach. However, significant differences in water solubility between DOX and ZnPc hinder their high drug-loading content within a unified carrier. Additionally, DOX’s systemic toxicity limits its therapeutic dosage, while low ZnPc loading shortens PDT duration, collectively restricting the efficacy of PDT and related synergistic therapy. This study aims to design a long-term PDT and CT synergistic therapy strategy to significantly improve the therapeutic effect and reduce the toxic side effects.Methods: We encapsulated ZnPc within biodegradable mesoporous silica nanoparticles (bMSN NPs) as the core, followed by electrostatic coating with tumor-targeting, DOX-loaded hyaluronic acid nanoparticles (DOX-HA NPs) to fabricate blackberry-like nanocomposites (DOX-HA/ZnPc-bMSN). In vitro and in vivo experiments determined tumor long-term PDT and CT synergistic therapy efficacy with DOX-HA/ZnPc-bMSN.Results: These nanocomposites achieved high ZnPc loading (DLC: 10.2% ± 1.6%) and efficient tumor accumulation, enabling prolonged systemic circulation (> 96 h) and sustained dual-drug release in vivo, realizing long-term photodynamic and CT synergistic therapy. In vitro studies showed a low combination index (CI = 0.26), with reactive oxygen species (ROS) production enhanced by 1.6-fold and 1.9-fold for ZnPc and DOX. The median lethal dose (LD50) of DOX-HA/ZnPc-bMSN nanocomposites (138.95 mg/kg) was 15.12 times higher than that of free DOX. Notably, in vivo studies demonstrated a 96.0% tumor inhibition rate has been achieved using ultralow doses of drugs (DOX: 0.2 mg/kg; ZnPc: 2 mg/kg). This long-term PDT and CT synergistic therapy elevated intracellular ROS levels, which not only induced apoptosis in tumor cells but also activated caspase-1, leading to direct GSDMD cleavage, GSDMD-N release, and pyroptotic tumor cell death.Conclusion: These nanocomposites dually trigger tumor cell apoptosis/pyroptosis, demonstrating potent therapeutic efficacy and safety for clinical translation. Keywords: blackberry-like nanocomposites, mesoporous silica nanoparticles, photodynamic therapy, chemotherapy, synergistic therapy